2022
DOI: 10.1002/chem.202202556
|View full text |Cite
|
Sign up to set email alerts
|

Observing Nearby Nuclei on Paramagnetic Trityls and MOFs via DNP and Electron Decoupling

Abstract: Dynamic nuclear polarization (DNP) is an NMR sensitivity enhancement technique that mediates polarization transfer from unpaired electrons to NMR-active nuclei. Despite its success in elucidating important structural information on biological and inorganic materials, the detailed polarization-transfer pathway-from the electrons to the nearby and then the bulk solvent nuclei, and finally to the molecules of interest-remains unclear. In particular, the nuclei in the paramagnetic polarizing agent play significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The DNP sample was then degassed with at least three freeze-pump-thaw cycles using a 3-way tap, and backfilled with Argon gas. 74,86 This procedure removes the paramagnetic 11 oxygen, which reproducibly improves the DNP enhancement factor by ~10 %. We could not implement the insert/eject cycle degassing method demonstrated in Kubicki et al because the rotor is likely to be blocked in our Bruker MAS DNP probe at lower temperatures.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The DNP sample was then degassed with at least three freeze-pump-thaw cycles using a 3-way tap, and backfilled with Argon gas. 74,86 This procedure removes the paramagnetic 11 oxygen, which reproducibly improves the DNP enhancement factor by ~10 %. We could not implement the insert/eject cycle degassing method demonstrated in Kubicki et al because the rotor is likely to be blocked in our Bruker MAS DNP probe at lower temperatures.…”
Section: Sample Preparationmentioning
confidence: 99%
“…[8][9][10] On the other hand, dynamic nuclear polarization (DNP) is an NMR sensitivity enhancement technique that can usually boost the NMR signals by several orders of magnitude. [11][12][13] In conclusion, Zhang et al have shown that 63/65 Cu NMR spectroscopy is a powerful tool for probing the copper environments within MOFs. By offering site-specic information about the coordination number and geometry of copper centers, it provides crucial insights into the factors governing the properties of MOFs.…”
mentioning
confidence: 92%
“…8–10 On the other hand, dynamic nuclear polarization (DNP) is an NMR sensitivity enhancement technique that can usually boost the NMR signals by several orders of magnitude. 11–13…”
mentioning
confidence: 99%
“…Although the FDM method has, in general, a poorer resolution, it is more affordable and easier to use relative to the resin-based SLA method. Both 3D printing technologies have been exploited in various NMR applications, ranging from fabricating MAS sample eject systems, 11 RF coils, [12][13][14][15] NMR sample tubes, 16 parahydrogen generator, 17 NMR sample degassing apparatus, 18,19 , NMR probeheads, 20 etc. Besides these examples, Xu et al have recently demonstrated that it is possible to fabricate MAS stator and drive caps using FDM, but only for > 3.5 mm system.…”
Section: Introductionmentioning
confidence: 99%